The Onlife Manifesto: rethinking the human condition in a hyperconnected era - Dewandre, Nicole (AoIR Selected Papers of Internet Research, 2013)
The pervasiveness of the changes induced by the deployment of ICTs is such that there is a need to rethink and reconfigure the concepts on which policy frameworks are built. Policy frameworks are still relying on omniscience/omnipotence utopia. It is suggested that Hannah Arendt’s framing of the human condition, based on natality and plurality can inspire a renewed sense of what it means to be human in a hyperconnected world. It opens the way for policy-making to shift away from a risk-based and parenting attitude, towards a literacy-based and partnering one, which can vibrate with the collective societal intelligence being expressed in the shaping, uptake, resistance and appropriation of ICTs by individuals and communities.